Aplikasi Penjualan Gerabah Berbasis Android Sebagai Media Pemasaran Online (Studi Kasus : UD Barokah Desa Penakak Masbagik) - Baiq Andriska Candra Permana; Siti Nurhaliza; Nurhidayati Nurhidayati; Mahpuz Mahpuz (Infotek: Jurnal Informatika dan Teknologi, 2022)
One of several forms of handicrafts that are widely sold in East Penakak Masbagik Village is pottery. UD. Barokah is one of the shops selling pottery products. However, the transaction system used so far still uses a manual system where buyers directly come to the pottery sales place to find or buy the preferred item. With the increase in the current electronic-based sales system, it is necessary for business actors to implement an online-based sales system (e-commerce) so that the marketing reach of goods becomes wider, one of them is by utilizing the android platform which is almost owned by most people these days. With the application of an Android-based online e-commerce system, it is expected to help increase sales of pottery at UD. Barokah especially to deal with the pandemic period where some conventional buying and selling activities are starting to decrease due to the limited community activities in public areas